Extended-CSP based analysis of non-repudiation protocols - HAN Zhi-geng; LUO Jun-zhou; WANG Liang-min (Tongxin xuebao)
A new formal method named extended-CSP approach was proposed for non-repudiation protocols.For check-ing its validity,both the well-known Zhou-Gollmann fair non-repudiation protocol presented by Zhou et al.in 1996 and one of its variant protocol were analyzed with this method.The result showed that this method not only could be used to analyze some security properties that could not be described by other methods,but also detected a known flaw of the protocol which could not be found by others,and meanwhile proved the variant protocol really enhancing its security.Finally,the correctness of this method was surveyed from the points of both its semantic and theory dependency,and some advantages in comparison with others were also showed together.